The effect of foot landing type on lower-extremity kinematics, kinetics, and energy absorption during single-leg landing - Joeng, J.; Shin, C. S. (Korean Journal of Sport Biomechanics, 2017)
Objective: The aim of this study was to examine the effect of foot landing type (forefoot vs. rearfoot landing) on kinematics, kinetics, and energy absorption of hip, knee, and ankle joints. Method: Twenty-five healthy men performed single-leg landings with two different foot landing types: forefoot and rearfoot landing. A motion-capture system equipped with eight infrared cameras and a synchronized force plate embedded in the floor was used. Three-dimensional kinematic and kinetic parameters were compared using paired two-tailed Student's t-tests at a significance level of .05. Results: On initial contact, a greater knee flexion angle was shown during rearfoot landing (p < .001), but the lower knee flexion angle was found at peak vertical ground reaction force (GRF) (p < .001). On initial contact, ankles showed plantarflexion, inversion, and external rotation during forefoot landing, while dorsiflexion, eversion, and internal rotation were shown during rearfoot landing (p < .001, all). At peak vertical GRF, the knee extension moment and ankle plantarflexion moment were lower in rearfoot landing than in forefoot landing (p = .003 and p < .001, respectively). From initial contact to peak vertical GRF, the negative work of the hip, knee, and ankle joint was significantly reduced during rearfoot landing (p < .001, all). The contribution to the total work of the ankle joint was the greatest during forefoot landing, whereas the contribution to the total work of the hip joint was the greatest during rearfoot landing. Conclusion: These results suggest that the energy absorption strategy was changed during rearfoot landing compared with forefoot landing according to lower-extremity joint kinematics and kinetics.